Pharmacological Correction of Severe Acute Pancreatitis with Pancreatogenic Diabetes Mellitus - Salivon, Hanna; Klymenko, Olena (The Ukrainian Scientific Medical Youth Journal, 2026)
Introduction. Acute pancreatitis (AP) is a complex pathology in emergency abdominal surgery associated with a high risk of systemic complications. The severe course of the disease is accompanied by pancreatic necrosis, systemic inflammatory response syndrome, and multiple organ failure. The metabolic consequences of massive destructive pancreatic damage often lead to the development of secondary pancreatogenic diabetes mellitus (type 3c), which manifests as profound insular insufficiency and critical hyperglycemia, significantly limiting therapeutic options and contributing to polypharmacy. Aim. The aim of this study was to analyze the clinical and pharmacological features of managing a patient with severe acute pancreatitis, pancreatic necrosis, and secondary pancreatogenic diabetes mellitus based on a clinical case. Materials and Methods. This paper presents a retrospective analysis of the medical history of a 60-year-old patient A. with severe AP. The severity of the condition was verified according to the 2012 Atlanta classification criteria by the presence of local destructive complications and transient renal dysfunction (serum creatinine 150 μmol/L). The comprehensive diagnosis included severe acute pancreatitis, focal pancreatic necrosis, splenic vein occlusion, cholangitis, reactive hepatitis, and subcompensated pancreatogenic diabetes mellitus. Abdominal CT confirmed focal changes in the gland and the presence of heterogeneous fluid collections. Upon admission, the glycemia level reached 20.9 mmol/L, and leukocytosis was 13.4 × 10⁹/L. Results. Pharmacotherapy in the intensive care unit included infusion detoxification (Sterofundin, Reosorbilact) and antibacterial coverage of the necrosis zones (ciprofloxacin, metronidazole), which was associated with a decrease in leukocytosis to 4.0 × 10⁹/L by the seventh day. Pancreatic secretion was suppressed with omeprazole and dalargin. To improve blood rheological properties and prevent thrombosis, given a fibrinogen level of 11.5 g/L, sodium enoxaparin and pentoxifylline were utilized. During the conservative treatment phase, due to an increase in transaminases (ALT 53 U/L, AST 72 U/L), hepatoprotectors (arginine glutamate, alpha-lipoic acid) were prescribed. Special attention was paid to the correction of carbohydrate metabolism. Due to the high risk of euglycemic diabetic ketoacidosis, glycemic control in the acute period was provided by insulin therapy. The administration of the SGLT2 inhibitor dapagliflozin at a dose of 10 mg/day was performed extremely cautiously only after the resolution of acute renal dysfunction (creatinine reduction to 102 μmol/L on the third day), stabilization of overall hemodynamics, restoration of hydration balance, and the patient's transition to oral nutrition. Conclusions. The described clinical case demonstrates the successful implementation of an individualized pharmacological strategy; however, proving the isolated efficacy of specific agents, such as dalargin or hepatoprotectors, is limited by the scope of a single observation. The use of SGLT2 inhibitors in the acute period of pancreatic necrosis cannot be considered a routine recommendation and requires dynamic monitoring of electrolytes, renal function, and acid-base status.